2012
DOI: 10.1074/jbc.m111.302786
|View full text |Cite
|
Sign up to set email alerts
|

cAMP-induced Mitochondrial Compartment Biogenesis

Abstract: Background: Mitochondrial biogenesis is a complex process, and its regulation is not well known. Results: cAMP-induced mitochondrial biogenesis through a decrease in the cellular phosphate potential is due to an increase in the glutathione redox status. Conclusion: Mitochondrial biogenesis is tightly linked to glutathione redox status. Significance: This is the first evidence for a glutathione redox control of a transcription factor involved in mitochondrial biogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…In the yeast Saccharomyces cerevisiae, the transcription factors Hap2p/3p/4p/5p -HAP complex-are the master regulators of mitochondrial biogenesis (7,8). This heteromeric complex relies on the binding to the promoter of target genes by recently demonstrated that PGC-1α is regulated by the glutathione redox state, as we previously showed for Hap4p (16,17). Previous studies also established the involvement of reactive oxygen species (ROS) and cAMP-dependent signaling in negative and positive regulation of the transcriptional regulators of mitochondrial biogenesis in both yeast and mammals (5,(18)(19)(20)(21).…”
mentioning
confidence: 86%
“…In the yeast Saccharomyces cerevisiae, the transcription factors Hap2p/3p/4p/5p -HAP complex-are the master regulators of mitochondrial biogenesis (7,8). This heteromeric complex relies on the binding to the promoter of target genes by recently demonstrated that PGC-1α is regulated by the glutathione redox state, as we previously showed for Hap4p (16,17). Previous studies also established the involvement of reactive oxygen species (ROS) and cAMP-dependent signaling in negative and positive regulation of the transcriptional regulators of mitochondrial biogenesis in both yeast and mammals (5,(18)(19)(20)(21).…”
mentioning
confidence: 86%
“…Previous work from our laboratory has shown a tight link between the activity of this signaling pathway and the cellular content in mitochondria [24,32,33,34,35]. It should be stressed here that throughout this review, mitochondrial content will refer to the cellular amount of mitochondrial cytochromes, a robust parameter that allows cellular quantitation of mitochondrial respiratory chain amount [36].…”
Section: Ros-induced Downregulation Of Mitochondrial Biogenesis Inmentioning
confidence: 99%
“…Exogenous cAMP addition to this strain increases HAP complex activity and thus mitochondrial biogenesis. cAMP triggers an enhancement of Hap4p stability, the regulator of the HAP complex [32]. Consequently, an increase in the cAMP pathway activity positively regulates mitochondrial biogenesis.…”
Section: Ros-induced Downregulation Of Mitochondrial Biogenesis Inmentioning
confidence: 99%
See 1 more Smart Citation
“…of the most important modulator of mitochondrial biogenesis in yeast, that is, the transcriptional coactivator Hap4p (49). It is likely that a reducing environment is fundamental for the function of PGC-1a as a coactivator of mitochondrial genes.…”
mentioning
confidence: 99%